Flow injection amperometric detection of ascorbic acid using a Prussian Blue film-modified electrode - Castro, SSL; Balbo, V. R.; Barbeira, PJS; Stradiotto, Nelson Ramos [UNESP] (Elsevier B.V., 2001)
The PB film-modified electrode was used as an amperometric detector for flow injection analysis of ascorbic acid. The modified electrode detector showed good sensitivity, stability and reproducibility. The calibration curve for ascorbic acid was linear over the concentration range from 5.0 x 10(-6) to 1.0 x 10(-3) mol l(-1) with a slope of 19.9 mA mol(-1) per litre and a correlation coefficient of 0.999. The detection limit of this method was 2.49 x 10(-6) mol l(-1). The relative standard deviation of six replicate injections of 2.5 x 10(-4) mol l(-1) ascorbic acid was 2.5%. The results obtained for ascorbic acid determination in pharmaceutical products are in good agreement with those obtained by using the procedure involving the reaction between triiodide and ascorbic acid. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: Prussian Blue; modified electrode; ascorbic acid; flow system; amperometric detector